PELAKSANAAN SISTEM MANAJEMEN MUTU (SMM) ISO 9001: 2008 DI SMK NEGERI 2 PENGASIH KULON PROGO TAHUN 2012 - Ipnugraha, Ipnugraha (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
ABSTRACT The purposes of this research are to reveal (1) the implementation of Quality Management System (QMS) of ISO 9001: 2008 in State Vocational High School 2 of Pengasih Kulon Progo, (2) the factors that support QMS of ISO 9001: 2008 in State Vocational High School 2 of Pengasih Kulon Progo, and (3) the factors that disturb the implementation of ISO 9001: 2008 in State Vocational High School 2 of Pengasih Kulon Progo. This study belongs to evaluation research which employed Context model, Input Process, and Product (CIPP). This research was conducted in State Vocational High School 2 of Pengasih Kulon Progo. The data resources were the school principal, the representative of Quality Management, the coordinator of School Counseling & Guidance, the head of administrative section, library coordinator, and the students. The research instruments were questionnaire, interview, and documents. Validation technique was by using triangulation, i.e triangulation data, situational data, and data gathering method. Data analysis techniques were qualitative data analysis based on Miles, Huberman dan Spradley, i.e. data analysis with data components which covered data reduction, data display, and conclusion drawing/ verification. The result of the research showed that (1) the implementation of QMS of ISO 9001: 2008 in State Vocational High School 2 of Pengasih Kulon Progo had been successful by considering the accomplishment the schoolquality objectives. In addition, the implementation of QMS of ISO 9001: 2008 for each component showed a high accompolishment, with an average score above 90%, (2) the supporting factors of QMS of ISO 9001: 2008 implementation in State Vocational High School 2 of Pengasih Kulon Progo consisted of human resources, RSBI fund, facilities, students high reading interst, provision of the relevant books and magazines for the students, (3) the obstacle factors of QMS of ISO 9001: 2008 implementation in State Vocational High School 2 of Pengasih Kulon Progo consisted of limited fund, students' mistake, less publication. Also, the document writing in working units were not match with the format of QMS of ISO 9001: 2008, the workload was too high, and there was sudden personnel replacement as well as limited area. Keywords: Quality Management System (QMS) of ISO 9001: 2008